Neonatal Care - Raines, Deborah; Iliodromiti, Zoe; Raines, Deborah; Iliodromiti, Zoe (IntechOpen, 2012)
This up-to-the-minute work is set against the backdrop of remarkable advances in Neonatal care. Including selected updates of contemporary issues concerning basic research and clinical practice, the present book investigates pathogenetic mechanisms implicated in fetal brain injury, sleep apnea, as well as covering the field of neonatal gastroenterology and nutrition care. It stimulates further research by fully acquainting the reader with the current knowledge and future perspectives in the sphere of an epidemiologic study for low birthweight, and the introduction of an effective, evidence-based innovational newborn program of care. Multidisciplinary specialists in Neonatology will find this book to be an essential resource, fundamental for a successful neonatal outcome.
English
Keywords: Paediatric medicine; Neonatal medicine